Investigating phoneme-dependencies of spherical voice directivity patterns - Pörschmann, Christoph; Arend, Johannes M. (The Journal of the Acoustical Society of America, 2021)
Dynamic directivity is a specific characteristic of the human voice, showing time-dependent variations while speaking or singing. To study and model the human voice's articulation-dependencies and provide datasets that can be applied in virtual acoustic environments, full-spherical voice directivity measurements were carried out for 13 persons while articulating eight phonemes. Since it is nearly impossible for subjects to repeat exactly the same articulation numerous times, the sound radiation was captured simultaneously using a surrounding spherical microphone array with 32 microphones and then subsequently spatially upsampled to a dense sampling grid. Based on these dense directivity patterns, the spherical voice directivity was studied for different phonemes, and phoneme-dependent variations were analyzed. The differences between the phonemes can, to some extent, be explained by articulation-dependent properties, e.g., the mouth opening size. The directivity index, averaged across all subjects, varied by a maximum of 3 dB between any of the vowels or fricatives, and statistical analysis showed that these phoneme-dependent differences are significant.